If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9x + -1) + -13(5x + -8) = x + 6 Reorder the terms: 4(-1 + 9x) + -13(5x + -8) = x + 6 (-1 * 4 + 9x * 4) + -13(5x + -8) = x + 6 (-4 + 36x) + -13(5x + -8) = x + 6 Reorder the terms: -4 + 36x + -13(-8 + 5x) = x + 6 -4 + 36x + (-8 * -13 + 5x * -13) = x + 6 -4 + 36x + (104 + -65x) = x + 6 Reorder the terms: -4 + 104 + 36x + -65x = x + 6 Combine like terms: -4 + 104 = 100 100 + 36x + -65x = x + 6 Combine like terms: 36x + -65x = -29x 100 + -29x = x + 6 Reorder the terms: 100 + -29x = 6 + x Solving 100 + -29x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 100 + -29x + -1x = 6 + x + -1x Combine like terms: -29x + -1x = -30x 100 + -30x = 6 + x + -1x Combine like terms: x + -1x = 0 100 + -30x = 6 + 0 100 + -30x = 6 Add '-100' to each side of the equation. 100 + -100 + -30x = 6 + -100 Combine like terms: 100 + -100 = 0 0 + -30x = 6 + -100 -30x = 6 + -100 Combine like terms: 6 + -100 = -94 -30x = -94 Divide each side by '-30'. x = 3.133333333 Simplifying x = 3.133333333
| 4x^2=11x+21 | | -3=10x+90-7x | | 168s=8 | | 6xy^2+7x^2y= | | -3+6+(-3)= | | 18-6b=10b+2 | | -3+(8)= | | 3(3x+5)-2(4x-5)=6(7x+1)-5 | | 3-8x=27 | | x(4x+16)=0 | | 7p=168 | | 63x^2-29x-4=0 | | 4w^2-16=0 | | 3v^2-21v=0 | | -9x^2+17x-8=0 | | 19x^2-12x=0 | | 24=44-x | | 10x^3-290x^2-620x=0 | | x+4+14x^2-32=0 | | 4x+4=-(x-19) | | 33+x(4x)=3(1) | | cos^2a-sin^2a=1-2sin^2a | | 8x^3-8=0 | | X-26=-11 | | 0=3x^2-17x+10 | | 8ln(9x)=32 | | 15x^6-95x^5+100x^4=0 | | 6.6x+5=5.6x | | x^2-30x-75=0 | | 2e^2x+5=8 | | 80x^2-296x+56=0 | | 4a=5-b |